Bitcoin and Cryptocurrency Technologies Arvind Narayanan, Joseph Bonneau, Edward Felten, Andrew Miller and Steven Goldfeder. Issue 8 (August 2016) - Unknown
Abstract : Crypto-currencies are an application of technology that severely divides opinion. For some, Bitcoin, Dogecoin, Litecoin and their ilk are enablers for criminals, terrorists, paedophiles and other undesirables, allowing them to profit from their dark deeds undetected. For others, the ability to buy and sell anonymously and beyond the reach of regulation, taxation and control is a form of freedom.